Popular concert album vol. 1 for orchestra Violoncello - QUINN, Alfred Price (The Boston Music Co., 1913)
Souvenir de VenisenTold at TwilightnThe Bim-bimsnAdieunBluettenLittle Concert WaltznLove songnCadiznWith powdered wig and hoop skirt